Pengaruh Salah Pilih Jurusan Terhadap Nilai Akademik Mahasiswa Program Studi BKI UIN Khas Jember - Wasilah, Wasilah; Azzaroh, Istofina; Rahmawati, Naely; Fitriana, Ani Qotuz Zuhro’ (CV. ITTC INDONESIA, 2023)
This research is a study that examines the causes and effects of the two variables, namely choosing the wrong major with student academic grades based on literature review with quantitative research dimensions, with the theme raised is The Effect of Choosing the Wrong Major on Student Academic Values ​​at BKI UIN KHAS Jember Study Program, There are two important questions in this research. First, is there any effect of choosing the wrong major for BKI UIN KHAS Jember study program students? Second, is there a relationship between choosing the wrong major and the academic grades of BKI UIN KHAS Jember students. The purpose of this study was the first to find out the percentage of students choosing the wrong major for the BKI UIN KHAS Jember study program on academic scores. Second, to find out the relationship between choosing the wrong major and the academic scores of BKI UIN KHAS Jember study program students. This study uses a quantitative approach using simple linear regression data analysis techniques, normality test, scatter plot heteroscedasticity test, and glejser heteroscedasticity test. Data collection techniques in this study used a questionnaire or questionnaire and literature (Library Research). In carrying out these three tests, the sample used was 31.1% of the total 2021 BKI students, namely 138 students. The results of the study concluded that choosing the wrong major (X) had no positive effect on academic value (Y) with an effect of 11%. This effect means that the higher the wrong choice of major will not affect academic grades.